2022
DOI: 10.1016/j.injury.2021.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Dual mobility cups do not reduce the revision risk for patients with acute femoral neck fracture: A matched cohort study from the Swedish Arthroplasty Register

Abstract: Introduction: Dual mobility cups (DMC) are gaining in popularity, as a method to reduce the risk of dislocation after fracture-related hip arthroplasty. Our aim was to compare revision rate in general, as well as due to dislocation and infection, after DMC and conventional THA due to femoral neck fracture, for each of the two groups of lateral and posterior approach. Materials and Methods: This observational cohort study based on the Swedish Arthroplasty Register (SAR) compared 2242 patients with dual mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Dual-mobility cups do not reduce the revision risk for patients with acute femoral neck fracture, as concluded by Rogmark and Nauclér in an observational cohort of 2,242 patients with dual-mobility cups compared with a matched cohort of 6,726 patients treated with a conventional total hip implant 1 . The authors reported that, with implant revision surgery as the outcome, they “could not detect any differences between a total hip arthroplasty with a dual mobility cup and one with conventional bearing.” Outcomes were similar and independent of whether the implants were inserted via a direct lateral or posterior approach as well as for subgroup analyses of revision for dislocation and infection.…”
Section: Implant Design and Related Outcomesmentioning
confidence: 78%
“…Dual-mobility cups do not reduce the revision risk for patients with acute femoral neck fracture, as concluded by Rogmark and Nauclér in an observational cohort of 2,242 patients with dual-mobility cups compared with a matched cohort of 6,726 patients treated with a conventional total hip implant 1 . The authors reported that, with implant revision surgery as the outcome, they “could not detect any differences between a total hip arthroplasty with a dual mobility cup and one with conventional bearing.” Outcomes were similar and independent of whether the implants were inserted via a direct lateral or posterior approach as well as for subgroup analyses of revision for dislocation and infection.…”
Section: Implant Design and Related Outcomesmentioning
confidence: 78%
“…Therefore, in the elderly, Garden I incomplete FNF may not exist. The elderly have decreased bone mineral density and osteoporosis, so their femoral necks are prone to fracture once they are subjected to external force [ 31 ]. Besides, the bones of the elderly have the features of decreased elasticity and enhanced brittleness, and the anatomical position of femoral neck is the turning part of force line [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…An observational cohort study based on the Swedish Arthroplasty Register (SAR) compared 2,242 patients with dual mobility cups (DMCs) and 6,726 with conventional total hip arthroplasty, all due to acute fractures. [ 10 ] The authors concluded that total hip arthroplasty with a DMC had similar outcomes in terms of revisions and, due to dislocation or infections specifically, as one with conventional bearing. Similar outcomes were regardless of the surgical approach.…”
mentioning
confidence: 99%